Meningkatkan Kemampuan Pemahaman Matematis Mahasiswa melalui Pembelajaran Kooperatif Tipe Formulate-Share-Listen-Create (FSLC) - Angra Meta Ruswana (IKIP Mataram, 2019)
Improving Students' Mathematical Understanding Ability through Formulate-Share-Listen-Create (FSLC) Cooperative Learning. The aim of this research is to examine and to describe improvement in students' mathematical understanding ability using cooperative learning of Formulate-Share-Listen-Create (FSLC) type. The study was conducted at the Mathematics Education Study Program of Galuh University on Level I students of the 2018/2019 Academic Year. The research method used is Quasi-Experiment. To get the research data, the instrument was used in the form of a test of mathematical understanding ability. Data analysis was performed on data n-gain to see the difference improvement in mathematical understanding ability. The results of the research showed that the improvement in students' mathematical understanding ability between students using cooperative learning of Formulate-Share-Listen-Create (FSLC) type was better than students who used conventional learning.